Hubungan Tingkat Pengetahuan Ibu Tentang Asupan Protein dengan Kejadian Stunting pada Balita - Anggun Sukma Azani; Wayan Canny Naktiany; Ni Made Wiasty Sukanty (Nutriology : Jurnal Pangan,Gizi,Kesehatan, 2023)
ABSTRACT HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG ASUPAN PROTEIN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS LINGSAR Anggun Sukma Azani Background: Toddlers are one of the age groups that are prone to nutritional problems. One of the nutritional problems that often occurs in toddlers is stunting. Stunting is a chronic malnutriyion in toddlers that causes children to be too short of children of the same age. Objective: The purpose of this study was to determine the relationship between the level of maternal knowledge about protein intake with the incidence of stunting in toddlers in the Lingsar Health Center work area. Method: The method used in this study is a type descriptive analytic observational research with a cross sectional approach. The population in this study was all stunted toddlers aged 24-59 months in Batu Mekar village, totaling 153 children. The sampling technique in this study was simple random sampling technique with a sample of 65 respondents based on the calculation results using the Lemeshow formula. Data analysis using spearman correlation test. Research Results: The results showed that there was a relationship between the mother’s level of knowledge about protein intake (p = 0.001), there was no relationship between maternal education (p = 0.671), there was no relationship between maternal work (p = 0.060), there was no relationship between maternal age (p = 0.509) and the incidence of stunting in the Lingsar Health Center work area. Conclusion: The conclusion in this study is that there is a significant relationship between the level of mother’s knowledge about protein intake and the incidence of stunting in toddlers in the Lingsar Health Center work area. Keywords: Protein Intake, Toddlers, Mother Knowledge, Stunting